PENDAMPINGAN MENGOPTIMALISASIKAN POTENSI UMKM DESA PASAR RAWA MELALUI DIGITALISASI - Siti Aqilah Sabita; May Sharah Athifah; Halimatussya’diyah Purba; Melinda Azizah; Ridho Ardiansyah Dalimunthe; Dwi Ardy Dermawan (Jurnal Padamu Negeri, 2026)
The main problems faced by MSMEs towards digitalization are the low level of human resources and unequal access to technology. Based on existing problems, this training aims to be a mentoring program to optimize the potential of Pasar Rawa Village MSMEs through digitalization. The subjects of this research were the people of Pasar Rawa Village, Kec. Gebang numbering 16 people. This activity was carried out using lecture, discussion and training methods. Based on the results of creating a Shopee account as a seller from the questions and answers, 90% of the 16 participants understood, while creating Canva from the questions and answers, 80% of the 16 participants understood. This is because the Shopee application has instructions to make it easier for users, whereas Canva doesn’t have instructions, it just depends on what we want to design.